European Union : Publication of Financial Sector Assessment Program Documentation-Technical Note on Progress with Bank Restructuring and Resolution in Europe. (IMF Staff Country Reports; Country Report ;, 2013)
This article is an analysis on the restructuring banking system of the European Union. The global financial crisis created the need to restructure by immensely reflecting weaknesses in the public, households, corporate, and other financial sectors. The restructuring includes the strengthening of bank resolution tools, the activation of nonperforming loans, the maintenance of macrofinancial framework, recovery of market access, and so on. The Executive Board recommends this transition of the European Union because this paves the way to financial stability globally.